The Current State of Pediatric Sports Medicine: A Workforce Analysis. Issue 2 (2nd April 2016) - Engelman, Glenn; Koutures, Chris; Provance, Aaron
ABSTRACT: Objective : Pediatric sports medicine is an evolving pediatric subspecialty. No workforce data currently exists describing the current state of pediatric sports medicine. The goal of this survey is to contribute information to the practicing pediatric sports medicine specialist, employers and other stakeholders regarding the current state of pediatric sports medicine. Methods : The Workforce Survey was conducted by the American Academy of Pediatrics (AAP) Division of Workforce and Medical Education Policy (WMEP) and included a 44-item standard questionnaire online addressing training, clinical practice and demographic characteristics as well as the 24-item AAP Council on Sports Medicine and Fitness (COSMF) questionnaire. Descriptive statistics were used to summarize all survey responses. Bivariate relationships were tested for statistical significance using Chi square. Results : 145 surveys were returned, which represented a 52.7% response rate for eligible COSMF members and board certified non-council responders. The most common site of employment among respondents was university-based clinics. The respondents board certified in sports medicine were significantly more likely to perform fracture management, casting and splinting, neuropsychological testing and injections compared to those not board certified in sports medicine. A large proportion of respondents held an academic/medical school appointment. Increases were noted in both patient volume and the complexity of the injuries the specialists were treating. Conclusion : This pediatric sports medicine workforce study provides previously unappreciated insight into practice arrangements, weekly duties, procedures, number of patients seen, referral patterns, and potential future trends of the pediatric sports medicine specialist.